2017
DOI: 10.1007/s00264-017-3557-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing patellar positioning during total knee arthroplasty: an anatomical and clinical study

Abstract: The placement of the patellar component during TKA differs from one patella to another. Thus, by defining the OCPP on a patient-by-patient basis, the surgeon should be able to reproduce the functional anatomy of the native patella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…Sambataro proposed the application of doppler ultrasound blood flow monitor to identify the subclavian artery and for the first time performed an ultrasound-guided supraclavicular brachial plexus block [2]. Assi C et al also found that the enhanced echo needle can significantly improve the visibility of deep vein catheterization, shorten the puncture time, improve the puncture success rate, and reduce the risk of puncture-related complications [3,4]. Lian proposed adding a small dose of fentanyl to local anesthetics for brachial plexus block, which significantly improved the success rate of the block, shortened the onset time, prolonged the sensory block time, and had no obvious side effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Sambataro proposed the application of doppler ultrasound blood flow monitor to identify the subclavian artery and for the first time performed an ultrasound-guided supraclavicular brachial plexus block [2]. Assi C et al also found that the enhanced echo needle can significantly improve the visibility of deep vein catheterization, shorten the puncture time, improve the puncture success rate, and reduce the risk of puncture-related complications [3,4]. Lian proposed adding a small dose of fentanyl to local anesthetics for brachial plexus block, which significantly improved the success rate of the block, shortened the onset time, prolonged the sensory block time, and had no obvious side effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous surgeons have advocated resurfacing the patella during total knee arthroplasty (TKA) to significantly reduce the revision rate, relieve pain, and improve patient-reported outcomes while remaining cost-effective ( 1 - 4 ). In contrast, a suboptimal surgical technique for resurfacing increases the risk of complications, such as patellar instability and clunk syndrome, anterior knee pain, or abnormal wear leading to prothesis loosening ( 1 , 5 , 6 ). Several principles should be followed to obtain satisfactory results, and replicating the original patellar ridge high point is one of them ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…To reproduce the native high point, surgeons choose to place the implant’s high point over the points on the patellar-cut surface projected from the high point of patellar ridge (HPPR) ( 5 , 10 ). This technique decreased the need for lateral retinacular release and improved patellofemoral prognosis ( 5 , 10 ). The HPPR positions vary widely, but mainly toward the medial aspect of the patellar cut ( 5 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations